Profiling hymenopteran venom toxins: Protein families, structural landscape, biological activities, and pharmacological benefits. (June 2022) - Guido-Patiño, Juan Carlos; Plisson, Fabien
Abstract: Hymenopterans are an untapped source of venom secretions. Their recent proteo-transcriptomic studies have revealed an extraordinary pool of toxins that participate in various biological processes, including pain, paralysis, allergic reactions, and antimicrobial activities. Comprehensive and clade-specific campaigns to collect hymenopteran venoms are therefore needed. We consider that data-driven bioprospecting may help prioritise sampling and alleviate associated costs. This work established the current protein landscape from hymenopteran venoms to evaluate possible sample bias by studying their origins, sequence diversity, known structures, and biological functions. We collected all 282 reported hymenopteran toxins (peptides and proteins) from the UniProt database that we clustered into 21 protein families from the three studied clades - wasps, bees, and ants. We identified 119 biological targets of hymenopteran toxins ranging from pathogen membranes to eukaryotic proteases, ion channels and protein receptors. Our systematic study further extended to hymenopteran toxins' therapeutic and biotechnological values, where we revealed promising applications in crop pests, human infections, autoimmune diseases, and neurodegenerative disorders. Graphical abstract: Image 1 Highlights: The hymenopteran toxin diversity includes 21 protein families from 81 species. Some toxins are shared across wasps, bees and ants, others are clade-specific. Their venoms contain membrane-active peptides, neurotoxins, allergens and enzymes. Hymenopteran toxins have been tested against a total of 119 biological targets. Hymenopteran toxins were predominantly evaluated as anti-infective agents.